The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/anae.13744
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring teamwork: a narrative review

Abstract: SummaryA narrative review was carried out to identify articles on monitoring of teamwork, with particular relevance to anaesthetists. The papers reviewed showed that team monitoring takes place both implicitly and explicitly in the anaesthetic environment. No single optimal model of teamwork monitoring for all situations was identified. Most of the studies identified were of a pre-intervention, post-intervention design, without randomisation or control group. Information shared during a formal briefing is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 71 publications
(90 reference statements)
0
10
0
3
Order By: Relevance
“…Respectful team communication and adaptability between different professional identities in the OR team can increase OR efficiency (Kaldheim & Slettebø, ; Weller & Boyd, ). Thus, the OR team can compensate for unexpected delays that may arise, for example in the case of patients with challenging anatomy (Rutherford, ). This study also revealed that OR nurses are reluctant to lead the OR team, regardless of how long experience they have and even in situations where they have most knowledge, for example positioning the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respectful team communication and adaptability between different professional identities in the OR team can increase OR efficiency (Kaldheim & Slettebø, ; Weller & Boyd, ). Thus, the OR team can compensate for unexpected delays that may arise, for example in the case of patients with challenging anatomy (Rutherford, ). This study also revealed that OR nurses are reluctant to lead the OR team, regardless of how long experience they have and even in situations where they have most knowledge, for example positioning the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Team skills and team behaviour in the OR have also been improved by team training (Gillespie, Chaboyer, & Murray, ; Nurok, Lipsitz, Satwicz, Kelly, & Frankel, ; Rutherford, ; Weaver et al, ). All inter‐professional team members must be included in teaching, simulation and implementation of tools and strategies (Baker, Salas, Battles, & King, ).…”
Section: Introductionmentioning
confidence: 99%
“…Coordination can be defined as the sequencing, synchronization and integration of team members' activities to ensure task accomplishment (Cannon-Bowers et al 1995;Rousseau et al 2006). It is the result of either an explicit effort by the team members which requires some kind of interaction between the members, or something that happens implicitly as an effect of standardized procedures and shared mental models (Johnson et al 2011;Rutherford 2017). Cooperation, by contrast, is defined as multiple team members working together on the same task accomplishment (Yeatts and Hyten 1998).…”
Section: Models Of Team Performance and Effectivenessmentioning
confidence: 99%
“…Attention was also devoted to organisational elements in monitoring (see Rutherford's article in this Supplement for further discussion of how to monitor the team ). An aspirational recommendation was included to encourage anaesthetic departments to allow anaesthetists working alone during long procedures to be relieved for meal and comfort breaks.…”
Section: Updates As Driven By Research: the Role Of This Supplementmentioning
confidence: 99%